An Analysis of Teacher Discipline at SMP Negeri 6 Luwuk, Indonesia: A Qualitative Study on Attendance, Punctuality, and Professional Responsibility (International Journal of Scientific Research and Management (IJSRM), 2024)
This study evaluates teacher discipline at SMP Negeri 6 Luwuk, focusing on attendance, punctuality, lesson preparation, participation in meetings, and task completion. It aims to identify strengths and weaknesses in teacher discipline and explore the impact of the principal’s leadership style on teacher performance. A qualitative approach was used, with data collected through observations, interviews with teachers and the principal, and documentation analysis.Findings show strong discipline in attendance, punctuality during teaching hours, and lesson preparation. However, issues exist in non-teaching punctuality, inconsistent participation in meetings, and delayed task completion. The principal’s democratic and charismatic leadership style fosters a positive work environment and enhances teachers’ responsibility.Despite overall discipline, improvements are needed in punctuality and task completion. The principal’s leadership supports a positive culture, but additional strategies are required to address weaknesses and optimize discipline. The study calls for targeted interventions to improve teacher discipline, ultimately enhancing school performance and educational outcomes.